New coumarin and dihydrocinnamic acid derivatives from two Malaysian populations of Micromelum minutum - Rahmani, Mawardi; Yap, Taufiq Yun Hin; Mohd Ismail, Hazar Bebe; Md. Sukari, Mohd Aspollah; Waterman, Peter G. (Elsevier Science, 1994)
Three novel compounds, two compounds and a dihydrocinnamic acid, have been isolated from two collections of Micromelum minutum and identified by means of NMR spectroscopy. A sample collected from Pahang gave the typical coumarin micromelin and a new dihydrocinnamic acid derivative of micromelin which was identified as 1,2-seco-dihydromicromelin. The second sample, collected from Kelantan, gave two new tetracyclic coumarins, microminutinin and 6-methoxymicrominutinin, which possess a fused bifurano system that appears to be derived by cyclization of a 7-oxygenated-8-(1,2-dimethyl)propylcoumarin precursor. The structure of microminutinin is revised from that proposed in a previous paper.